Water rights pricing in the Philippines: Issues, challenges and way forward - Maria Francesca Mercedes D. Grabador (University of the Philippines, School of Economics (UPSE), 2024)
Water is critical not only to economic progress and sustainable development but most importantly, to human survival. Yet, the way water is valued suggests an inexhaustible supply, when the opposite is true. This paper examines if water rights in the Philippines are underpriced and looks at how these can be valued at full economic cost. It finds that water resources in the Philippines are essentially given no value since the administrative cost-recovery approach is used to determine fees for water permits and water charges. Moreover, through the analysis of different pricing models used in other countries' water markets, this study also presents the core components of an economic pricing model for water rights. While the establishment of water markets may represent the first best solution to water scarcity, it is an ideal solution in an ideal setting; thus, second and third best solutions are also presented. The study concludes that while it is not possible to immediately price water rights at its full economic cost, it may be done gradually, starting with the adoption of volumetric pricing and strengthening the institutional capacity of the National Water Resources Board (NWRB).
Keywords: Q21; Q25; Q28; O53; O57; 330; water permits; water rights; water rights trading; water rights markets; economic pricing models for water rights; water resource management; volumetric pricing